MASA ‘IDDAH PASCA PERCERAIAN DALAM KACAMATA TEORI MUBADALAH - Daud Muhsin, Muhammad Najib; Azhari, Hulaimi (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2023)
'Iddah is a period determined by syara' for a woman after a divorce to refrain from marrying another man. This provision is always associated with reasons to know the possibility of getting pregnant or in other words, to know the cleanliness of the uterus. However, looking at today's increasingly modern world, it is possible to detect pregnancy in a short time. With this it is clear that the purpose of 'iddah is not only knowing the cleanliness of the uterus. Another problem is that this 'iddah provision only applies to women, because it is supported by texts found in the Qur'ān and the Prophet's Hadith which only mention women. Whereas in a text, if one gender is the cause for the goodness or badness of the other sex, then according to the rules of inclusion, both can be included in the same message in a reciprocal, reciprocal way, or what Faqihuddin calls mafhūm mubādalah. In this study, the authors tried to analyze Faqihuddin Abdul Kodir's mafhūm mubādalah method for the problem of 'iddah for husband and wife.